Development and psychometric testing of Indonesian clinical assessment tool (In-Cat) for student nurses - Purwarini, Justina (The Journal of Practice Teaching and Learning, 2021)
In clinical nursing, students apply knowledge gained from classroom experience to real life situations. This educational model is experiential in nature, where patient learning experiences are selected based on the successful learning process. Hence, the competencies anticipated at a certain level are achieved in accordance with the objectives of knowledge. Purpose: This study was, therefore, aimed at developing a valid clinical assessment tool to guide the education system, and evaluate nursing students’ performance during practice in Indonesia. Methods: This research employed an exploratory sequential mixed method research design. Result: The transcripts generated from Focus Group Discussions and in-depth interviews showed three major areas of competence to be achieved while undergoing clinical practice. These ought to be combined with learning outcomes on the Competency-Based Curriculum in Indonesia, and subsequently reprocessed, to establish the final results, comprising 37 items. The study shows IN-CAT as acceptable (Scale-CVI= 0.9), indicating the agreement is adequate (Cohen’s kappa= 0.795), and satisfactory (The Cronbach’s alpha= 0.949). Conclusion: The results initially specify the scale as a reliable and valid measurement tool, with the potential for use in the assessment and evaluation of clinical competence amongst nursing students. Based on the feedback from teachers and students, The assessment tool demonstrates clarified learning objectives, improved focus, and enhanced the evaluation objectivity.